Crioterapia melhora a função dos membros superiores e a qualidade de vida em indivíduos com síndrome do impacto do ombro - Siqueira Junior, Aristides Leite (Universidade Federal de São Carlos, 2015)
Background: O ombro é a articulação mais susceptível à lesões no corpo humano, afetando grande parte da população e, com isso, é de extrema importância a inserção de novos tratamentos para as afecções desta articulação. Objective: To evaluate the effects of cryotherapy on the serum levels of inflammatory mediators (IL-1β, IL-6, IL-10 and TNF-α), the pressure pain threshold (PPT), the function and quality of life in patients with SIS. Methods: 30 subjects were selected (15 with SIS and 15 healthy subjects). The cryotherapy (ice package for 20 min) was used only in the SIS group and it was applied once a day for four consecutive days on the affected shoulder. Two assessments were performed: one 72 hours pre-cryotherapy and the other 96 hours post-cryotherapy. The serum levels of the inflammatory mediators were assessed by ELISA method (10 ml of blood) and the PPT was measured with a digital pressure algometer in six points (upper trapezius, deltoid, tibialis anterior, infraspinatus, supraspinatus and coracoid process). The upper limb function and quality of life were assessed by the questionnaires of Disabilities of the Arm, Shoulder and Hand (DASH) and the Western Ontario Rotator Cuff Index (WORC), respectively. Results: No serum concentrations of inflammatory mediators were detected in the SIS and control groups. There was no difference in the PPT (p> 0.05) between groups, but there was an increase in post-cryotherapy PPT at the upper trapezius and the supraspinatus in the SIS group. The pre-cryotherapy group showed less functionality and quality of life in DASH and WORC questionnaires, respectively (p <0.01), compared to the control group. Cryotherapy improved both the function of the SIS group (DASH p = 0.02) and the quality of life, (WORC p = 0.001), when compared to pre-cryotherapy values. Conclusion: The results of this study indicate that SIS is a local condition, restricted to the shoulder structures and does not alter the serum levels of inflammatory factors. Cryotherapy applied daily over the shoulder affected by SIS presented a beneficial and lasting effect, improving the upper limb function, quality of life, the PPT of some muscles and can be recommended as a treatment option. Study limitations: The examiner was not blind to the groups in the DASH, WORC and PPT assessments. The isolated effect of compression, used for fixing the ice packs was not evaluated.
Keywords: Ombro; Dor; Inflamação; Hipotermia; Fisioterapia; Pain; Shoulder; Inflammation; Physical therapy; Hypothermia; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL